High-stakes Recordkeeping and Relationality: Conversations from the Sex Work Activist Histories Project - Allard, Danielle; Ferris, Shawna; Lebovitch, Amy; Clamen, Jenn; Hughes, Micheline (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2024)
The Sex Work Activist Histories Project (SWAHP) is an interdisciplinary research and recordkeeping initiative to record and disseminate the radical knowledges, activist expertise, and important social movement histories created by activists connected to the Canadian sex worker rights movement. This paper explores how stakeholders of SWAHP work together ethically, and maintain good relations with each other when engaging in what we call high-stakes recordkeeping. Our discussions consider both the divergences or differences between academic and non-academic project partners, our convergence or common ground, and the bridges we have built between academic and non-academic concerns and practices to establish and develop methodologies and practices that inform SWAHP’s ongoing collaborations and sex-work activist histories, archives, and related activisms. We consider how to be mutually accountable to our varied and complex analytical and affective positionalities in the specific context of working ethically and relationally in high-stakes recordkeeping. We conclude by considering the relevance of these lessons to other contexts of community-led archiving and research. This paper is a lightly edited transcript of the speaker notes from a 2021 CAIS/ACSI (Allard, Ferris, Lebovitch, Clamen, and Hughes, 2021) panel presentation. Project partners are identified individually in their article sections to share, highlight, and preserve what is unique about each project partners’ perspective and voice, and to make explicit how we work together.